Warung Kopi sebagai Ruang Publik dari Masa Ke Masa Di Kota Medan - Lukitaningsih Lukitaningsih; Devi Juliani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This study aims to determine the background of the emergence of modern coffee shops in the city of Medan, the development of modern coffee shops in the city of Medan, and the contribution of modern coffee shops as a public space for the people of Medan. This research uses the Heuristic method with a qualitative approach. The type of research used is field research with data collection techniques through direct observation of 7 modern coffee shops and 1 traditional coffee shop in the city of Medan, interviews with 38 informants and literature studies. The results of the study showed that the emergence of modern coffee shops in Medan could not be separated from the influence of the presence of Starbucks coffee outlets, the influence of sachet coffee, urban lifestyle and the growing popularity of locally produced coffee such as Aceh coffee and North Sumatra specialty coffee. The development of the number of modern coffee shops in the city of Medan since 2013 every year shows a significant increase. Until 2019 there were at least 282 modern coffee shops in the city of Medan. Nowadays, modern coffee shops contribute as a place for visitors to do some activities, such as a coffee shop, a place to work on assignments, a meeting place, a place to hang out, a place for celebrations, or a place to simply meet friends.